How to ensure the provision of social inclusive public transport bus services? a strategic case study in Lisbon - Sacoor, H.; Arsenio, E.; Cardoso, E.; Barateiro, J. (49th European Transport Conference (ETC 2021), 2021)
Public transport companies operating in cities pursue their mission in a context of increasingly complexity, dealing with conflicting goals, scarce financial resources, and high uncertainty levels, recently aggravated by the current pandemic caused by COVID-19. In this context, the research question can be posed as follows: • How can public transport companies redefine their services and rethink their strategies to ensure that socially inclusive services can be continuously provided along with other sustainability goals? To answer the above research question, the research methodology comprised a comprehensive review of public transport planning at the strategic and operational levels along with strategic management and performance evaluation methods in public transport. A case study was carried out that included the development of an enhanced state-of-the-art method – the Balanced Scorecard (BSC) approach and its application to the context of a main Public Transport (Bus) Company managed by the Lisbon municipality in Portugal. The research reported in this paper is part of the research and innovation project - Integrative Learning from Urban Data and Situational Context for City Mobility Optimization (ILU), that includes the collaboration of two research institutes and the city of Lisbon. The BSC developed is anchored in a sustainable mobility vision and translates the strategic vision of the company into four main perspectives - financial, customer (user-centric), internal processes and learning and growth, for which strategic objectives, performance indicators, goals and initiatives are defined. The strategic map of the company was developed using the ArchiMate software which makes the cause-effect management relationships visible to all employees and stakeholders. Strategic objectives were then linked to key performance indicators of several types for enabling monitoring purposes. For example, considering the customer’s perspective, the set of strategic objectives “Promote greater accessibility by public transport”, “Retain customers”, “Maximize customer satisfaction” are related to the value proposition to the customer and include indicators such as the percentage of vehicles meeting accessibility standards for users with reduced mobility, Total passenger transported, customer satisfaction index, etc., aligned with ensuring quality of service standards. One of the advantages of the BSC tool is to account for the impact of disruptive events (not to increase social inequalities) and keep the company aligned with its pre-defined sustainable mobility strategy goals. Therefore, it enables linking the accomplishment of each objective connected to a set of performance indicators that are continuously monitored for planning purposes. Considering the limited number of case studies applying the BSC to public transport companies, research results are important to shed light to this knowledge field and contribute to policy and mobility planning purposes.